Implementation of the Tahsin Method in Improving Quality Fashohah Students Studying Qur'an Hadith at Madrasah Ibtidaiyah - Nadlir Nadlir; Beauty Dewi Negari; Imamatut Ta'dzimah; Durroh Nasihatul Ummah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
While learning Al-Quran Hadith, some students often encounter several obstacles,one of which is the aspect of reading the Al-Quran. Not a few of them are still notfluent when reading the Al-Quran and have not applied it fashohah appropriate,as well as the application of makharijul letters and tajwid. The purpose of writingthis research is to see the level of success of the tahsin method in improving andimproving students' reading of the Al-Quran so that students can read the Al-Qurancorrectly according to the pronunciation of the hijaiyah letters and the correctrules for reciting tajwid. This research uses the method of Systematic LiteratureReview (SLR) which means reviewing the results of previous research regardingthe application of the tahsin method to improve quality fashohah. The results ofthis research show that the tahsin method can improve the quality of fashohahstudents, one of which is in the application of Al-Quran Hadith learning. This isbecause the tahsin method is suitable for various groups, especially children, forwhom at the elementary school or madrasah ibtidaiyah level it is the foundationfor further learning.